Persistence of Low Serum Iron and High Total Iron Binding Capacity in Pregnant Women - Wahed, F; Latif, SA; Uddin, MM; Mahamud, MM; Sarker, D; Hossain, MZ (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2):132-6The abstract of this article is available on the PubMed website